Um novo registro de rincossauro juvenil para o Triássico Superior do sul do Brasil: análise taxonômica e implicações ontogenéticas - Morais, Jossano de Rosso (2024)
Rhynchosaurs are reptiles with peculiar anatomy widely known in the fossil record from the Triassic Period. However, individuals in early developmental stages are rare. Thus, the present work aims to reveal the anatomy of the specimen CAPPA/UFSM 0295, which represents the smallest individual ever recorded for the group. The work describes the specimen, which includes a skull fragment and incomplete mandibular rami, and is one of the smallest ever recorded for the group, measuring 25 mm in length if the skull were complete. CAPPA exhibits several characteristics shared with the more apical rami of Rhynchosauridae, more specifically Hyperodapedontinae, including a ventrally closed lower temporal fenestra, a maxilla extensively overlapped by the jugal laterally, and a tall mandible. Its maxilla shows both conical and pyramidal teeth, and the jugal possesses a marked crista anguli oris. CAPPA/UFSM 0295 displays ontogenetic features indicative of an immature individual, such asthe presence of only one row of teeth lateral and medial to the main groove on the maxillary tooth plate, with little or no indicative of tooth wear. This makes the specimen the first record of a periate individual for Hyperodapedontinae, and the oldest record of an archosauromorph hatchling. Additionally, the specimen allows the recognition of the ontogenetic variation of characters of phylogenetic importance, thus guiding future studies on rhynchosaur evolution